World War I - Willmott, H. P. (New York : DK, 2009)
Discusses the causes and consequences of World War I, features accounts of some of the conflict's most significant battles, and includes original documentary and visual sources, including letters from the front, war poetry, and photographs.
Includes index.
Adult
Keywords: World War I, -- 1914-1918 -- Pictorial works; World War I -- 1914-1918 -- History